Meningkatkan Kemampuan Memahami Cerita dan Teks Drama Tentang Penggunaan Pecahan Uang Rupiah dan Pecahan Ukuran dengan Metode Pembelajaran Sosiodrama di Kelas III SDN Kepuh Klagen Wringinanom Gresik - Suwanti (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
Learning will take place effectively and efficiently if it is supported by the teaching role that regulates learning strategies well and maximally. In presenting learning methods, a teacher cannot be confined to just one type of technique. The old paradigm that considers the teacher as the only source and center of information, as well as students is just like an empty glass that can be filled with anything according to the instructor's wishes or likened to a white paper that can be written whatever according to the instructor's wishes, may need to be reviewed. When students enter the classroom, the teacher must be aware that inside the student has been embedded and built up information, knowledge and experience they have acquired outside the classroom from interaction with their environment. This study aims to: 1) Describe the activities of teachers in improving the ability to understand stories and drama texts about the use of rupiah denominations and fractions of size with sociodrama learning methods in Class III Kepuh Klagen Wringinanom Gresik SDN. 2) Describing the activities of students in learning activities increases the ability to understand stories and drama texts about the use of rupiah denominations and fractions of size with the sociodrama learning method in Class III of Kepagen Klagen Wringinanom Gresik SDN. 3) Describe learning with sociodrama learning methods to improve the ability to understand stories and drama texts about the use of rupiah denominations and fractions of size in Class III SDN Klagen Wringinanom Gresik SDN. This research is a classroom action research conducted collaboratively. Designing problem situations, and ways to collaborate with children, is the main focus of meetings that occur between teachers and researchers. This research was carried out at the Kepagen Klagen Wringinanom Gresik Elementary School with the address Bureng Kidul, Kepuhklagen, Kec. Wringinanom, Gresik Regency, East Java 61176. The subjects of this study were Class III students of 25 children. The study was conducted in the even semester of the school year 2018/2019, for 3 months (April, May, June 2019). Procedures for cyclical action research are: 1) planning, 2) implementation, 3) observation, and 4) reflection, through a series of cycles. Data collection through observation (observing), artifacts and documents (testing) and nonstandard tests. Test instrument items with validity test, reliability test, calibration test (level of difficulty) and distinguishing test. the entire process of data analysis is interactive using the Miles and Huberman models with the final mix method analysis. The results of the study concluded: 1) The teacher's activity experienced an increase in Pre-Action to get results of 60.71 percent and increased in Cycle I by 75.71 percent and increased in Cycle II by 89.29 percent; 2) Student activity has increased in Pre-Action to get a result of 45.71 percent and increase in Cycle I by 68.57 percent and increase in Cycle II by 86.43 percent; 3) The average value of the test (Classical Absorption) has increased in Pre-Action to obtain a result of 76.6 percent and increase in Cycle I by 82.2 percent and increase in Cycle II by 90.6 percent. Classical Learning Completion has increased in Pre-action gets 64 percent and increases in Cycle I by 80 percent and increases in Cycle II by 92 percent.